Design and Development of Novel Azo Prodrugs using Various Permutations and Combinations of 5- and 4-Aminosalicylic Acids for Inflammatory Bowel Disease: A Colon-Targeted Approach - Suneela, Dhaneshwar; Gaurav, Vadnerkar; Himanshu, Rai (Inflammation & Allergy-Drug Targets (Discontinued), 2013)
Novel carrier-linked azo prodrugs of 4 and 5-aminosalicylic acids (4-ASA and 5-ASA respectively) using the same drugs as carriers in different permutations and combinations were designed for targeting colon affected with inflammatory bowel disease (IBD). Improved hydrophilic nature of the prodrugs assisted in minimizing their absorption in upper GIT and efficient delivery of the active drugs to colon as evidenced from their stability in aqueous buffers (pH 1.2 and 7.4) and upper GIT homogenates with 68-91% release on incubation with rat cecal matter. Amongst the series, 4A4AAZ (prodrug of 4-ASA with 4-ASA) at a dose of 53 mg/Kg was found to be the most promising candidate as it substantially alleviated the quantifying markers of colonic inflammation in TNBS-induced experimental colitis in Wistar rats. Moreover it displayed significantly lower GI toxicity (at ten times higher dose). 5-ASA- induced pancreatitis and sulfapyridine-induced adverse effects on liver that are characteristic of sulfasalazine were not observed with 4A4AAZ. It could be explored further as a potential candidate for IBD patients intolerant to pancreatitis induced by oral administration of 5-ASA.
Keywords: 4-Aminosalicylic acid